Camels : causing trouble tour. (2006)
Poster promoting a rock band tour. Features an image of a camels travelling in a hotrod. Event venues, and dates which appear at the foot, have been partially covered by a label which gives details of the Caringbah event only.
The Camels are an Australian rock band from Sydney, New South Wales, formed in late 1999 by brothers Jamie Holt and Tim Holt (guitar & vocals), along with Matt Smedley (bass) and Dave Springer (drums).They recorded their self-funded debut album All You Ever Needed with producer Tim Powles (The Church) in October 2002. They began touring Australia extensively in the second half of 2004. The band was commissioned to write 3 songs for a documentary about Sydney's Bra Boys surf gang from Maroubra. In 2006 the band recorded three tracks for the Bra Boys documentary and songwriter Jamie Holt contributed the film's theme song "My Brothers' Keeper" and 18 other pieces for the original score. The film was released on the 15th of March 2007, and has become Australia's highest-grossing documentary--adapted from Wikipedia, viewed 19 January 2017.
Acquired as part of a collection of ‘gig’ posters accumulated by a Sydney secondhand music dealer during the early 2000s. Many of the posters promote performances at two well known Sydney music venues: Brass Monkey in Cronulla and Bizzo’s in Caringbah.
Keywords: Camels (Musical group) -- Posters; Rock music -- Australia -- Posters; Music -- Australia -- Posters; Posters, Australian; Australian; Alternative Rock